Zuclopenthixol Induced Ischemic Priapism: Case Report and Review of Literature - Elias Mansour; Samer Danaf; Daniel Ghoussainy; Georges Assaf; Imad Ghantous; Fouad El-Khoury (Tehran University of Medical Sciences, 2023)
Objective: Present a case of zuclopenthixol associated priapism, literature review and focus on the stuttering priapism entity as a potential serious complication as well as providing information about possible preventive treatments. Case report: A 44 year-old male patient with history of cocaine abuse with associated priapism presents with acute painful erection after starting zuclopenthixol for treatment of a psychotic episode. This episode was later followed by many other similar episodes defined as stuttering priapism. Conclusion: Acute ischemic priapism is a potential serious side effect of antipsychotics that physicians especially psychiatrists needs to be aware of especially if the patient has previous episodes in order to prevent reoccurrence.